Intralesional ultrasound‐guided combined treatment with triamcinolone plus lincomycin in hidradenitis suppurativa: A pilot study. Issue 6 (14th July 2020) - Fania, Luca; Clemente, Antonio; Sampogna, Francesca; Mazzanti, Cinzia; Pallotta, Sabatino; Panebianco, Annrita; Sordi, Donatella; Caggiati, Alessio; Cassotta, Gabriella; Tiezzi, Alessandro; Cristiano, Lara; Zecchi, Viola; et al.
Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory, disease of the hair follicle. Intralesional corticosteroid treatment in HS patients has been reported, and while several data described this route of administration as an efficient delivery system, its efficacy is still debated. The aim of this study was to explore the clinical efficacy and the effect on quality of life (QoL) of an innovative intralesional treatment in HS patients. This was an interventional prospective study. The treatment consisted of two intralesional ultrasound‐guided injections of triamcinolone plus lincomycin, at baseline and after 2 weeks. Lesions and QoL were evaluated at baseline and at 4 weeks following intralesional therapy. All clinical variables of 36 HS patients significantly improved after 4 weeks. Mean values of the visual analog scale (VAS) pain decreased from 4.6 to 1.5, P = .027. The Bodily Pain (BP) scale of the Short‐Form Health Survey (SF‐36) significantly improved from 36.2 at baseline to 53.9 at 4‐week follow‐up ( P < .001). On a scale from 0 to 10, over 90% of the patients gave a satisfaction score of 8 or more. This combination of corticosteroids and antibiotics delivered intralesionally seems to be effective, as it improved both patient‐ and physician‐reported outcomes.